Genome-Wide Variation, Candidate Regions and Genes Associated With Fat Deposition and Tail Morphology in Ethiopian Indigenous Sheep - Ahbara, Abulgasim; Bahbahani, Hussain; Almathen, Faisal; Al Abri, Mohammed; Agoub, Mukhtar Omar; Abeba, Ayelle; Kebede, Adebabay; Musa, Hassan Hussein; Mastrangelo, Salvatore; Pilla, Fabio; Ciani, Elena; Hanotte, Olivier; et al. (Frontiers in Genetics, 2019)
Abstract Variations in body weight and body fat distribution are associated with feed quality and quantity, thermoregulation and energy reserve. Ethiopia is characterised by distinct agro-ecologies and human ethnic farmer’s diversity of ancient origin which have impacted on the variation of its livestock species. Here, we investigate the autosomal genome-wide profiles of 11 Ethiopian indigenous sheep populations using the Illumina Ovine 50K SNP BeadChip assay. Populations from The Caribbean, Europe, Middle East, China and western, northern and southern Africa were included addressing globally, the genetic variation and history of Ethiopian sheep populations. Population structure, PCA and phylogenetic analysis separate the Ethiopian indigenous fat-tail sheep from the North African and Middle Eastern fat-tailed sheep. It indicates two main genetic backgrounds and supports two distinct genetic history for the African fat-tailed sheep. Within Ethiopia, our results indicate that the short fat -tailed do not represent a monophyletic group. Four genetic backgrounds are present within Ethiopian sheep but at different proportions among fat-rump sheep, long fat-tailed sheep from western Ethiopia and long fat-tailed sheep from southern Ethiopia. Ethiopian fat-rump sheep were also found to share a common genetic background with Sudanese thin-tail sheep. Selection signature analysis identified eight candidate genomic regions that spanned genes influencing growth traits and fat deposition (NPR2, HINT2, SPAG8), embryonic development of tendons, bones and cartilage (EYA2, SULF2), regulation of body temperature (DIS3L2, LIN28B) and the control of lipogenesis and intracellular transport of long-chain fatty acids (SREBF1 and FABP3). Our findings indicate that Ethiopian indigenous fat-tail sheep represent a distinct genepool and an important resource for understanding the genetic control of fat metabolism and associated physiological processes.